Sólarhringl og suðið í okkur - Huldar Breiðfjörð 1972- (Bjartur, 2019)
Huldar Breiðfjörð is a prolific Icelandic author of many critically acclaimed novel such as Góðir Íslendingar and Múrinn í Kína who has of late been writing manuscripts for movies and tv series, Undir trénu f.ex. Anyhow, in this book he like in Góðir Íslendingar is dealing with Icelanders and what exactly is the Icelandic condition.
Keywords: Lebensphilosophie; Isländer; Mentalität